THE ECONOMIC IMPACT OF MULTILINGUALISM - Tursunxo‘jayeva Moxigul Maxmud qizi; Tursunova Ozodaxon To’raxon qizi (Ustozlar uchun, 2025)
Multilingualism plays a crucial role in shaping global economies by enhancing productivity, fostering innovation, and promoting trade. This paper investigates the economic benefits associated with multilingual societies, workplaces, and educational policies. Through an analysis of existing literature, we explore the macroeconomic and microeconomic implications of multilingualism, emphasizing its role in globalization and workforce competitiveness.